Crystal structure of cis-dichlorido(1,4,8,11-tetraazacyclotetradecane-κ4N)chromium(III) (oxalato-κ2O1,O2)(1,4,8,11-tetraazacyclotetradecane-κ4N)chromium(III) bis(perchlorate) from synchrotron data - Dohyun Moon (Acta Crystallographica Section E: Crystallographic Communications, 2016)
In the asymmetric unit of the title compound, [CrCl2(C10H24N4)][Cr(C2O4)(C10H24N4)](ClO4)2 (C10H24N4 = 1,4,8,11-tetraazacyclotetradecane, cyclam; C2O4 = oxalate, ox), there are two independent halves of the [CrCl2(cyclam)]+ and [Cr(ox)(cyclam)]+ cations, and one perchlorate anion. In the complex cations, which are completed by application of twofold rotation symmetry, the CrIII ions are coordinated by the four N atoms of a cyclam ligand, and by two chloride ions or one oxalate bidentate ligand in a cis arrangement, displaying an overall distorted octahedral coordination environment. The Cr—N(cyclam) bond lengths are in the range of 2.075 (5) to 2.096 (4) Å while the Cr—Cl and Cr—O(ox) bond lengths are 2.3358 (14) and 1.956 (4) Å, respectively. Both cyclam moieties adopt the cis-V conformation. The slightly distorted tetrahedral ClO4− anion remains outside the coordination sphere. The supramolecular architecture includes N—H...O and N—H...Cl hydrogen bonding between cyclam NH donor groups, O atoms of the oxalate ligand or ClO4− anions and one Cl ligand as acceptors, leading to a three-dimensional network structure.